INVESTMENT ATTRACTIVENESS OF ENTERPRISES: EVALUATION, ORGANIZATIONAL SUPPORT, MANAGEMENT COMPETENCES - Vilhutska, R.B.; Lema, H.V.; Fedorchak , O.Y.; Mykhaylyshyn, L.I. (The actual problems of regional economy development, 2020)
The article presents the existing approaches to defining the essence of the concept of "investment attractiveness of the enterprise", "organizational structure of the enterprise" and "development of employee competencies". Approaches to the interpretation of the essence of investment attractiveness of the enterprise by different authors are revealed. The method of forecasting the market value of the enterprise on the basis of modification of the linear regression model of the relationship between the value of shares of a particular enterprise and the amount of dividends paid is considered. The implementation of this method can be carried out in three stages: the formation of data series for regressors and the dependent variable, the cycle is associated with the need to obtain the equation of the required accuracy and the calculation of the market value of the enterprise in the future. A method of economic assessment of the investment attractiveness of the enterprise based on the calculation of the expected future market value of its shares is proposed. The essence of the reference investment instrument is also given. The impact of the restructuring of the organizational structure of management on the development of employee competencies is reflected. It is proposed to consider the indicator of mobility of organizational management structures, which indicates how the change in the capacity of the organizational management structure affects the indicators of economic development of the enterprise. It demonstrates how the current OSU meets the needs of the enterprise. The stages of implementation of the learning process at the enterprise are given and characterized, which consists of such stages as: collection and processing of information, choice of teaching methods, evaluation of training effectiveness.